Options for the livestock sector in developing and emerging economies to 2030 and beyond - International Livestock Research Institute (World Economic Forum, 2019)
This paper focuses on emerging and developing nations. It argues that making use of the great diversity of livestock systems along with “enablers for transformation” creates opportunities to translate today’s rapid growth in demand for livestock-derived foods into rapid progress in sustainable and equitable development. We recognize that while most stakeholders in livestock development have the same end in mind – the evolution of a sustainable, responsible and efficient livestock sector – the great diversity of livestock species and production systems will necessitate very different starting points and trajectories. This diversity should be approached not as a problem to be solved but as a requirement for meeting societies’ protein and other needs.